Mattradisjoner og spor etter status på Island fra landnåmstid til middelalder - Belyst ved komparative analyser av faunamaterialet på fire utvalgte gårder - Boge, Mona Karin (The University of Bergen, 2018)
Denne masteroppgaven tar for seg mattradisjoner og endringer i disse på Island i landnåmstid og tidlig middelalder. Oppgaven baserer seg hovedsakelig på faunamaterialet funnet ved fire utvalgte gårder i nord samt sørvest utenfor fastlandet. Sammen med faunamaterialet, husstrukturer og funn av andre arkeologiske gjenstander er det utført en komparativ analyse for å vurdere den sosiale statusen ved hver av de fire gårdene. The focus in this thesis is to investigate the faunal material sampled from excavations at four different farms from the Viking age through early medieval times on Iceland. The farms include Granastaðir in Eyjafjarðarsýsla, Skuggi in Eyjafjörður, and Hofstaðir, all from the northern part of Iceland. Herjólfsdalur is located southwest on the island Vestmannaeyjar Faunal material tells us something about the food culture and traditions in a society. Also it can provide information about the economy and substance strategies on each farm. The faunal material will be considered in relation to the status of each of the four farms listed, and whether it`s possible to use faunal material as an indicator to determine status. Other factors like house structures and stables for husbandry will also be considered together with the zooarchaeological material. Another issue in this thesis is whether it`s possible to detect any changes throughout time, and if so, what does this changes mean and how does the changes fit with adaption of the life on Iceland. A comparative analysis between the four farms is used to look at status and changes in farm economy in a broader perspective. Arkeologi mastergradsoppgave MAHF-ARK ARK350